2012
DOI: 10.1186/1746-1596-7-33
|View full text |Cite
|
Sign up to set email alerts
|

The expression patterns and correlations of claudin-6, methy-CpG binding protein 2, DNA methyltransferase 1, histone deacetylase 1, acetyl-histone H3 and acetyl-histone H4 and their clinicopathological significance in breast invasive ductal carcinomas

Abstract: BackgroundClaudin-6 is a candidate tumor suppressor gene in breast cancer, and has been shown to be regulated by DNA methylation and histone modification in breast cancer lines. However, the expression of claudin-6 in breast invasive ductal carcinomas and correlation with clinical behavior or expression of other markers is unclear. We considered that the expression pattern of claudin-6 might be related to the expression of DNA methylation associated proteins (methyl-CpG binding protein 2 (MeCP2) and DNA methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 41 publications
0
29
1
Order By: Relevance
“…Little is known about the molecular mechanisms that drive the development and prog ression of malignant tumors within fibroadenomas. Comparative studies that analyzed various molecular markers in fibroadenomas and breast carcinomas failed however to identify the potential drivers [35,36]. However, a clonality study of Kuijper et al [37] indicated that fibroadenomas possessed a potential to progress in an epithelial direction (carcinoma) or in a stromal direction (phyllodes tumor).…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about the molecular mechanisms that drive the development and prog ression of malignant tumors within fibroadenomas. Comparative studies that analyzed various molecular markers in fibroadenomas and breast carcinomas failed however to identify the potential drivers [35,36]. However, a clonality study of Kuijper et al [37] indicated that fibroadenomas possessed a potential to progress in an epithelial direction (carcinoma) or in a stromal direction (phyllodes tumor).…”
Section: Discussionmentioning
confidence: 99%
“…MeCP2 regulates cell proliferation, cell growth and apoptosis in prostate cancer cells (Bernard et al 2006;Yaqinuddin et al 2008). Apart from these reports, MeCP2 has also been linked to cervical cancer (Wang et al 2013) and ductal carcinomas (Xu et al 2012a). Altered MeCP2 expression in gastric cancer has been shown to be mediated by the action of miR-212 (Wada et al 2010).…”
Section: Cancermentioning
confidence: 99%
“…Moreover, claudin-4 has been reported to be highly unregulated in gastric cancer, with an association between the up-regulation of claudin-4 and lymph node metastasis [14]. Claudin-6 protein is significantly down-regulated in breast invasive ductal carcinomas and is an important correlate with lymphatic metastasis [15]. Together such observations suggest that claudin protein expression may be related to the survival and invasion of cancer cells and may have significant clinical relevance.…”
Section: Introductionmentioning
confidence: 99%